In-process monitoring of powder bed fusion with fringe projection - Southon, Nicholas Edward (2020)
Additive manufacturing (AM) is a family of manufacturing techniques that are increasingly being used for the production of high performance or highly customised parts. Greater adoption of AM for end-use manufacturing is hampered by unpredictable process outcomes and limitations on both geometry and build orientation. Powder bed fusion is currently used to manufacture end use parts in both metal and polymer, with greater industrial adoption expected. However, it is widely acknowledged in literature that process control and, therefore, process monitoring, are needed to make powder bed fusion more suitable for widespread use in manufacturing. If a defect can be detected during the process, it can either be repaired in-situ or process parameters can be changed to reduce the occurrence of further defects. A record of the detected defects in a part could also contribute to a quality certification procedure for applications with strict certification requirements, such as aerospace part production.